MHD Modeling of the Background Solar Wind in the Inner Heliosphere From 0.1 to 5.5 AU: Comparison With In Situ Observations - Y. X. Wang; X. C. Guo; C. Wang; V. Florinski; F. Shen; H. Li; M. Blanc (Space Weather)
Abstract The accurate prediction of solar wind conditions in the interplanetary space is crucial in the context of both scientific research and technical applications. In this study, we simulate the solar wind throughout the heliosphere from 0.1 to 5.5 astronomical units (AU) with our improved heliospheric magnetohydrodynamics (MHD) model during the time period from 2007 to 2017. The model uses synoptic magnetogram maps as input to derive the inner boundary conditions based on a series of empirical relations such as the Wang‐Sheeley‐Arge (WSA) relation. To test the performance of this model, we compare the simulation results with in situ measurements from multiple spacecraft including ACE/WIND, Solar TErrestrial Relations Observatory, Ulysses, Juno, and MErcury Surface, Space ENvironment, GEochemistry, and Ranging at different latitudes and heliocentric distances. There is an overall agreement between the model results and solar wind observations at different latitudes and heliocentric distances. Statistical analysis for Year 2007 reveals that our model can predict most of the corotation interaction regions, high‐speed streams, and magnetic sector boundaries at 1 AU. In addition, the bimodal structure of the solar wind for different latitudes is well reproduced by the model which is consistent with Ulysses data. This study demonstrates the capabilities of our heliosphere model in the prediction of the large‐scale structures of the solar wind in the inner heliosphere, and the model can be used to predict the ambient solar wind at locations of planets in the solar system such as Earth and Jupiter.